Biofilm thickness restraint carriers enhance free nitrous acid inhibition for partial nitritation. Issue 2 (13th May 2022) - Schopf, Alexander; Christensson, Magnus; Piculell, Maria; Tian, Xin; Delatolla, Robert
Abstract: Ammonia is a deleterious pollutant present in municipal wastewater that can be hazardous if released into the environment. There is a need for the development of novel processes to advance ammonium removal technologies. Partial nitritation (PN) and anaerobic ammonia oxidation (anammox) are modern treatment processes that can be combined to provide energy-efficient ammonia removal; however, these processes have been shown to be challenging to implement as a two-stage system. New methods to achieve steady PN need to be discovered. Free nitrous acid (FNA) exposure has been explored as a possible strategy for achieving PN; however, exposure time to FNA and FNA dosage is dependent on the treatment system. For biofilm technologies, such as the moving bed biofilm reactor and biofilm characteristics, including biofilm thickness, can cause inconsistent results. Therefore, this study compares defined maximal biofilm thickness with undefined biofilm thickness and their capacity to achieve PN using FNA. This study found that a defined maximal biofilm thickness designed carrier maintained a thin biofilm capable of achieving PN after FNA exposure while the undefined biofilm thickness designed carrier was not suitable for stable PN. HIGHLIGHTS: There is a need for new and robust strategies to achieve stable partial nitritation using attached-growth technologies. Thin biofilm has shown potential for enhanced free nitrous acid (FNA) inhibition of nitrite-oxidizing bacteria (NOB) activity. Maximal biofilm thickness and undefined thickness carriers studied for FNA inhibition. Maximal biofilm thickness carriers show NOB inhibition at 3 h of FNA exposure. Undefined thickness carriers are not capable of achieving NOB inhibition with FNA exposure. Graphical Abstract